જો $x = {{\sqrt 5 + \sqrt 2 } \over {\sqrt 5 - \sqrt 2 }},y = {{\sqrt 5 - \sqrt 2 } \over {\sqrt 5 + \sqrt 2 }},$ તો $3{x^2} + 4xy - 3{y^2} = $
${1 \over 3}[56\sqrt {10} - 12]$
${1 \over 3}[56\sqrt {10} + 12]$
${1 \over 3}[56 + 12\sqrt {10} ]$
એકપણ નહીં
${{12} \over {3 + \sqrt 5 - 2\sqrt 2 }} = $
જો ${a^x} = bc,{b^y} = ca,\,{c^z} = ab,$ તો $xyz=$
જો ${a^x} = {b^y} = {(ab)^{xy}},$ તો $x + y = $
${{\sqrt {(5/2)} + \sqrt {(7 - 3\sqrt 5 )} } \over {\sqrt {(7/2)} + \sqrt {(16 - 5\sqrt 7 )} }}=$
સમીકરણ ${(x)^{x\sqrt x }} = {(x\sqrt x )^x}$ ના ઉકેલની સંખ્યા મેળવો.